Media concentration and democracy : why ownership matters - Baker, C. Edwin (Communication, society, and politics., 2007)
"Objections to concentrated ownership of the mass media are widespread. Often, however, critics merely point to the fact of huge and growing media conglomerates without explaining precisely why this is bad. This book fills the gap in the critique of concentration. Firmly rooting its argument in democratic and economic theory, the book argues that a more democratic distribution of communicative power within the public sphere and a structure that provides safeguards against abuse of media power provide two of three primary arguments for ownership dispersal. It also shows that dispersal is likely to result in more owners who will reasonably pursue socially valuable journalistic or creative objectives rather than a socially dysfunctional focus on the "bottom line." The middle chapters answer those, including the current Federal Communications Commission, who favor "deregulation" and who argue that existing or foreseeable ownership concentration is not a problem. The final chapter evaluates the constitutionality and desirability of various policy responses to concentration, including strict limits on media mergers."--Jacket